Changes in host gene expression patterns underpin responses of the coral Stylophora pistillata to nutrient stress - Tessa M. Page; Cecilia D’Angelo; Jörg Wiedenmann; Gavin L. Foster (Scientific Reports)
Abstract The availability and stoichiometry of dissolved nutrients are known to have a significant effect on coral growth, biomineralisation, and stress tolerance. However, previous mechanistic studies have focused primarily on the photosynthetic symbionts. Here we studied the physiological and transcriptomic responses of the coral Stylophora pistillata exposed to four different concentration combinations of dissolved inorganic nitrogen (N) and phosphorus (P) over a period of eight weeks. Despite no significant effects on coral growth or calcification, corals from low P conditions bleached and had significantly fewer symbionts than those from high-phosphate treatments. Low P concentrations induced upregulation of ion transmembrane transporter activity, and downregulation of transcripts involved in phospholipid biosynthesis, protein processing, and protein maturation. Further, all enriched biological processes were related to phosphate metabolism. Our results suggest that S. pistillata controls a variety of molecular pathways to counteract the negative effects of insufficient nutrient supply.